THE PROSPECTS OF MICRO-INSURANCE IN THE RURAL AREAS OF NIGERIA - Mohammed, Aliero Haruna; Mukhtar, Shuaibu (European Scientific Journal, ESJ, 2012)
This study investigates the prospects of micro-insurance in the rural areas of Nigeria, while Kebbi State was used as case study. The data used in this study is cross sectional and was collected from a sample of 190 respondents, who were contacted through a structured questionnaire. The data collected was analyzed using logit regression model and the study revealed that income level, educational attainment and property ownership as well as availability of infrastructural facilities in the rural areas, the prospects of Micro-Insurance in the rural areas of Nigeria. The study recommended that income level of the rural dwellers should be taken into consideration while setting premium, efforts to provide, at least basic education in the areas, should be intensified it is also suggested that serious mobilization and sensitization should precede the introduction of Micro-Insurance. Micro-insurance in rural areas should place more emphasis on farming, being the major occupation in the rural areas. As such we recommended for Agricultural Micro-insurance in rural Nigeria, at least at start.